Family physicians’ continuing professional development activities: current practices and potential for new options - Lindsay, Elizabeth Ann; Wooltorton, Eric; Hendry, Paul; Williams, Kathryn; Wells, George (Canadian Medical Education Journal, 2016)
Background: As part of needs assessment processes, our Faculty of Medicine (FOM) continuing professional development office investigated the differences between physicians who do and those who do not frequently participate in planned group learning to gain insight into their interest in new forms of continuing professional development (CPD). Method: We sent a 19 item questionnaire to 485 randomly selected physicians of the 1050 family physicians in Eastern Ontario. The questionnaire examined present participation and satisfaction with CPD activities and perceptions regarding the potential impact of those; and appetite for new opportunities to meet their learning needs. Results: Of the 151 (31%) physicians responding, 61% reported attending at least one FOM group learning program in the past 18 months (attenders) and 39% had not (non-attenders). Non-attenders indicated less satisfaction (p = 0.04) with present opportunities and requested development in newer approaches such as support for self-learning, on-line opportunities, and simulation. Conclusions: Although there are high levels of satisfaction with the present CPD system that predominantly offers large group learning options, a substantial number of physicians expressed interest in accessing new options such as personal study and on-line resources.